Pelatihan Saving Money Management Bagi Siswa SMA - Rita Amelinda; Eva Oktavini; Hartoni; Phendikin Hendrick Yonathan; Deni Iskandar; Lambok David Ricardo Tampubolon (FEB-UP Press, 2024)
By looking at the demographic point of view, Indonesia's population is dominated by the productive age at 65.79%. The quality of education determines a better Human Development Index in the future. OJK recorded Indonesia's financial literacy in 2022 at 49.68 percent. Generation Z has an efficient way to access information and transactions in allocating their funds. However, Santo Leo II school has a gap issue in students’ lifestyle who tend to be consumptive. In addition, the low understanding of money management is also a crucial problem that is considered important to be educated in training. Therefore, the Faculty of Economics and Business Ukrida organized a training on Friday, July 21, 2023 which was attended by 69 students. The activity received quite high enthusiasm. Through this activity, participants' understanding of saving management and financial planning has measurably increased. However, the understanding of the importance of emergency funds has not yet had a significant impact. Keywords: financial planning, financial literacy, saving management